Rare dinars from the last Abbasid period - Alsheikh, Ali Kadhim (Al-Adab Journal, 2022)
This research is one of the important studies that dealt with rare Islamic Coins (Dinnar) in the last Abbasid era. It investigates Islamic Coins (Dinnar( which studied for the first time. The importance of this study Comes from the importance of target city (Hilla). The studied coins are related to Abbasid Caliph (Al Nasir Ledein Allah 275-622 H.D) In addition, the research investigates the Shape and size of this Dinnar and its Artistic aspects such as Calligraphy and de Coration.